Negative Shocks and Political Parties’ Territorial Demands: The Institutional Roots of Party Competition - Amat, Francesc; Rodon, Toni (Frontiers in Political Science, 2021)
Why do political parties set an extreme or a more moderate position on theterritorial dimension? Despite previous works have paid recent interest on the dy-namics of the political competition on the territorial dimension, we know much lessabout the factors that lead to a centrifugal or a centripetal party competition on thesame dimension. In this article, we offer a new way of understanding it: we arguethat parties’ policy position on the decentralization continuum not only dependson the level of territorial decentralization, but also on the the credibility of theinstitutional agreement established through the country’s constitutional rigidity. Ifthe original territorial pact does not guarantee that the majority group will have its“hands tied” so that it does not reverse the territorial agreement, political partieswill have incentives to adopt more extreme positions on the territorial dimension.We test this argument with a dataset covering around 460 political parties clus-tered in 28 European countries from 1999 to 2019 and by exploiting the fact thatthe 2008 economic crisis unleashed a shock on the territorial design. Our resultsconfirm our expectations. We show that both the federal deal and the credibilityof the institutional arrangement through constitutional rigidity are necessary con-ditions to appease parties’ demands on the territorial dimension. Our results haveimportant implications for our understanding of how institutions shape politicalcompetition along the territorial dimension.